Python for Data Visualization: Pengembangan Soft Skill Literasi Data Mahasiswa Universitas Megarezky - Risal, Andi Alviadi Nur; Arifin, Dafrid Cahyadi; Utama, Muh Ilham Budi; Amir, Nurdzakirah (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Activity aims to improve the data literacy and visualization skills of students of the Information Systems Study Program at Megarezky University through Python for Data Visualization training: Developing Soft Skills for Data Literacy of Megarezky University Students. The training was carried out in the form of an interactive workshop based on direct practice, including the use of Pandas, Matplotlib, and Seaborn. The results of the pre-test and post-test showed an increase in technical understanding of 38%, with 82% of participants being able to apply Python syntax independently. In addition, mini projects arranged in groups showed the development of soft skills, such as critical thinking, teamwork, and visual communication. As many as 100% of groups compiled data narratives logically and communicatively. The output of the activity in the form of project reports and infographics can be used as portfolios and teaching materials. The final questionnaire showed that 96% of participants assessed the application training and expressed interest in taking further training. This activity is a strategy to strengthen students' data competencies based on practice. Keywords: Python, data visualization, data exploration, students, soft skills